Filsafat Pendidikan Dan Relevansinya Dengan Pendidikan Islam Modern: Telaah Ontologi - Niswah Atqiya Maulidya Niswah Atqiya Maulidya (Universitas Islam Balitar, 2025)
Abstract This article examines an ontological review within the philosophy of education and its relevance to the development of modern Islamic education. Ontology, as a branch of philosophy that studies the nature of being, serves as an essential foundation for understanding the reality of education, particularly concerning the nature of human beings, knowledge, God, and the aims of education. Through a library research approach based on the literature of educational philosophy and various contemporary studies on Islamic education, this article analyzes how an ontological understanding can strengthen the philosophical foundation of Islamic education amid the challenges of modernity. The findings indicate that Islamic education must be grounded in the principle of tawhid (the oneness of God), view humans as beings with an innate disposition (fitrah) encompassing physical, intellectual, and spiritual dimensions, and regard knowledge as a divine gift in which religious and general sciences are not dichotomized. The relevance of ontology in modern Islamic education is reflected in the development of holistic educational goals, the integration of values within the curriculum, the teacher’s role as a murabbī (educator and moral guide), and the formation of learners who are intellectually, morally, and spiritually balanced. This article concludes that an ontological approach can restore Islamic education to its authentic orientation, namely the formation of the insān kāmil (the complete human being), who is capable of facing contemporary developments without losing Islamic identity. Keywords: Ontology; Philosophy of Education; Islamic Education; Modernity Abstrak Artikel ini mengkaji telaah ontologis dalam filsafat pendidikan serta relevansinya terhadap pengembangan pendidikan Islam modern. Ontologi sebagai cabang filsafat yang membahas hakikat keberadaan menjadi dasar penting dalam memahami realitas pendidikan, khususnya terkait hakikat manusia, ilmu, Tuhan, dan tujuan pendidikan. Melalui penelitian studi pustaka terhadap literatur filsafat pendidikan dan berbagai kajian kontemporer tentang pendidikan Islam, artikel ini menganalisis bagaimana pemahaman ontologis dapat memperkuat fondasi filosofis pendidikan Islam di tengah tantangan modernitas. Hasil kajian menunjukkan bahwa pendidikan Islam harus berlandaskan prinsip tauhid, memandang manusia sebagai makhluk berfitrah dengan dimensi jasmani, akal, dan ruhani, serta menempatkan ilmu sebagai anugerah ilahiah yang tidak terpisah antara ilmu agama dan ilmu umum. Relevansi ontologi dalam pendidikan Islam modern terlihat pada pengembangan tujuan pendidikan yang holistik, integrasi nilai dalam kurikulum, peran guru sebagai murabbī, serta pembentukan peserta didik yang seimbang secara intelektual, moral, dan spiritual. Artikel ini menyimpulkan bahwa pendekatan ontologis mampu mengembalikan pendidikan Islam kepada orientasi hakikinya, yaitu membentuk insan kamil yang mampu menghadapi perkembangan zaman tanpa kehilangan identitas keislamannya. Kata kunci: Ontologi; Filsafat Pendidikan; Pendidikan Islam; Modernitas.